Understanding the role of SOCS signaling in neurodegenerative diseases: Current and emerging concepts. (October 2017) - Cianciulli, Antonia; Calvello, Rosa; Porro, Chiara; Trotta, Teresa; Panaro, Maria Antonietta
Graphical abstract: Highlights: SOCS signaling is able to control the inflammatory response acting on various signaling pathways. SOCS proteins are involved in the regulation and progression of immune responses in microglia cells. There is a clear connection between neurodegenerative diseases and SOCS-regulated STAT pathway. SOCS signaling represent a considerable potential for the development of therapeutic strategies. Abstract: Suppressor of cytokine signaling proteins (SOCS) are a family of intracellular cytokine inducible proteins, consisting of eight members. They are involved in the complex control of the inflammatory response through their actions on various signaling pathways, including the JAK/STAT and NF-κB pathways. A series of studies has shown that SOCS proteins are involved in the regulation and progression of immune responses in microglia cells. The accumulated data suggest that modulation of SOCS expression could be a target for drug development aimed at controlling inflammation in the brain. This review focuses on the current understanding of SOCS proteins involvement in inflammation-based neurodegenerative diseases and their role as therapeutic targets in future approaches.